On the synonymy of Dymantis Stål, 1861 and Eomyrochea Linnavuori, 1982 and resulting nomenclatural changes (Hemiptera: Heteroptera: Pentatomidae) - Kment, Petr; Rider, David A. (Zootaxa, 2015)
The Afrotropical genus-group taxa Dymantis Stål, 1861 and Eomyrochea Linnavuori, 1982 (Hemiptera: Heteroptera: Pentatomidae: Pentatominae: Myrocheini) are confirmed as objective synonyms, both sharing the same type species: Dymantis subvittata Stål, 1861. As a result, Dymantis (= Eomyrochea, syn. confirm.) is downgraded to a subgenus of Myrochea Amyot and Serville, 1843 and a new genus, Neodymantis gen. nov., is established for Dymantis sensu Linnavuori (1982) (type species Halys plana Fabricius, 1803). The following new combinations are proposed: Myrochea (Dymantis) subvittata (Stål, 1861), comb. nov., Neodymantis aias (Linnavuori, 1982), comb. nov., Neodymantis grisea (Jensen-Haarup, 1931), comb. nov., Neodymantis plana (Fabricius, 1803), comb. nov., and Neodymantis relata (Distant, 1898), comb. nov. The known distribution of the species involved is reviewed and the following new records are provided: Neodymantis aias from the Democratic Republic of the Congo, N. plana from Ghana and Togo.